The impact of Brexit on financial markets: Taking stock - Michaela Hohlmeier; Christian Fahrholz (International Journal of Financial Studies, 2018)
The UK's withdrawal from the EU will have far-reaching consequences on the European economy. However, the ultimate consequences of Brexit, especially for financial markets, depend on the final agreement, which is still under negotiation. Currently, regulated financial services can be provided across borders under simplified conditions. Without a special agreement, these EU passports cease to apply for business activities between both jurisdictions after Brexit. The EU third-country regimes for non-EEA companies are too few and too unsecure for intensive relations in trade and services. Knowing that London is the leading global financial center, an adequate agreement needs to be found, to ensure affordable and sufficient financial services for business, investors, and consumers. Unfortunately, it appears almost impossible to find solutions for the often contrary interests and various thematic areas in the remaining negotiating period-a no deal scenario becomes more likely. As a result, market participants have started to adapt structures and processes accordingly, by relocating certain functions to the EU27. Nevertheless, it is up to the negotiators to reach an agreement, which achieves the best possible outcome for all affected parties taking into account the opportunity costs of a failure in present Brexit negotiations.
Keywords: F30; F40; G15; G20; 330; Brexit; financial markets; transitional agreement; third country regimes; regulation; European Union; United Kingdom; derivatives; banking services; investment services; insurance services